2009
DOI: 10.1177/107769900908600204
|View full text |Cite
|
Sign up to set email alerts
|

Health News Agenda Building: Journalists' Perceptions of the Role of Public Relations

Abstract: This study uses a nationwide survey of health journalists (N = 774) to explore the agenda-building process in health news, examining how journalists develop story ideas, value expert source characteristics, and perceive the acceptability of using public relations materials. Results indicate that intermedia agenda setting may be a stronger influence on agenda building than are information subsidies, and that journalists rate characteristics associated with public relations training as important in expert sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
74
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 25 publications
8
74
4
4
Order By: Relevance
“…A search in the database of the Flemish Journalists Association showed that only 14 journalists are specialized in health news, which confirms the international tendency that increasingly generalists instead of specialized journalists cover health issues (Len-Rios et al, 2009). In addition, it showed that mainly print media invest resources in specialized health journalists.…”
Section: Research Questions and Methodologymentioning
confidence: 87%
See 4 more Smart Citations
“…A search in the database of the Flemish Journalists Association showed that only 14 journalists are specialized in health news, which confirms the international tendency that increasingly generalists instead of specialized journalists cover health issues (Len-Rios et al, 2009). In addition, it showed that mainly print media invest resources in specialized health journalists.…”
Section: Research Questions and Methodologymentioning
confidence: 87%
“…Especially experts such as health scientists but also health professionals such as medical doctors are shown to be the chosen sources. Journalists also routinely search medical and scientific journals for story ideas and information (Len-Rios et al, 2009;Rowe et al, 2003;Van Trigt et al, 1994). Several authors find an explanation for this finding in the often complex and technical matter of health news.…”
Section: Sourcing Practices In Health News: An Old or New Story?mentioning
confidence: 99%
See 3 more Smart Citations